Principles and practice of veterinary technology (Mosby, 2004)
This book contains comprehensive coverage of all major content areas studied by veterinary technology students and implemented by veterinary technicians. It is expanded from the first edition with new topics and updated information reflecting the latest improvements in patient care and client interaction.